Administration of N-acetylcysteine for contrast-induced acute kidney injury; an updated mini-review - Sam Mirfendereski; Mahboobe Taghipour; Farshad Yadollahi; Hadi Taghavinejad; Mahdieh Ahmadnia (Society of Diabetic Nephropathy Prevention, 2024)
Contrast-induced acute kidney injury (CI-AKI) is a potential complication of medical imaging procedures that use contrast media. It is important to identify and manage risk factors for contrast-induced nephropathy and to monitor patients for signs of renal damage after contrast administration. N-acetylcysteine (NAC) can prevent CI-AKI through multiple mechanisms of action, including reducing oxidative stress, improving renal hemodynamics, reducing inflammation, reducing apoptosis and fibrosis, reducing oxidative stress-induced DNA damage, reducing tubular cell injury, and reducing renal tubular cell apoptosis. However, the exact mechanisms of action may vary based on the specific study or context. Further research is needed to fully elucidate the molecular mechanisms of NAC in preventing CI-AKI.